Preparation of Highly Ordered Fiber Micropatterns by Assembly of Electrospun Nanofiber Segments. (11th August 2016) - Liu, Jun; Wang, Hua; Chang, Meng-Jie; Du, Hui-Ling
Abstract : A novel method for fabricating highly ordered fiber micropatterns by assembly of electrospun nanofiber segments was described. Polymethylglutarimide (PMGI) fiber segments with an average length of 3  µ m were prepared by combining electrospinning with subsequent sonication treatment. Afterwards, the fiber segments dispersed in water were assembled on Norland optical adhesive (NOA) templates with different microstructural sizes and shapes, allowing formation of spatially uniform nanofibrous micropatterns on flat glass substrate. Regular fiber microarrays were produced when the feature size of NOA template was larger than 30  µ m for square and strip geometry. In each microdot, the fiber segments had several layer thicknesses. This new method, which can prepare fiber micropatterns for different materials and microstructures, is suitable for functional device and cell biology applications.